Cultural probes method in design research: creativity in sketches - Černevičiūtė, Jūratė; Liebutė, Lina (Creativity Studies, 2022)
Despite the abundance of methods and models, the design research is still often entangled in concepts irrelevant to design practice. This paper rethinks the discourse of design research and the evolving role of a designer. The most important attempts to build a design as an academic discipline are mentioned, along with research communities that are operating in the field of design. Art-and-design-based approach in design research in Donald Schön’s works on architecture and design practice, rises the importance of sketches in the creative idea generation. Implementing sketching techniques into the cultural probes, as one of an art-and-design-based research method, opens up ways to innovative design solutions. This paper discusses the relationship between the method and sketching in the context of the case study “When Nobody Sees”. Sketching is discussed as an art-based tool for problem-setting.